One-Pot Synthesis of Aminated Benzo-Fused Heterocycles and N-Substituted Dibenzothiophenes via Copper-Catalyzed Ullmann Type Reaction - Alelaiwi, Sawsan H. (ACS Omega, 2021)
[Image: see text] We report here a direct and effective method to synthesize a primary amine of several polycyclic aromatic compounds. This reaction has been achieved through copper (I)-catalyzed Ullmann C–N coupling. Furthermore, this strategy allows the synthesis of new N-substituted dibenzothiophene derivatives through the coupling of 2-bromodibenzothiophene with various ranges of primary and secondary amines. The use of inexpensive catalysts, aqueous ammonia as the convenient source of ammonia and ligand free, makes this protocol environmentally and economically favorable for the synthesis of these compounds.